Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Audio Visual Terhadap Penguasaan Kompetensi Pengetahuan IPA - Kadek Hery Okta Rivaldi; DB.Kt. Ngurah Semara Putra; I Ketut Adnyana Putra (Jurnal Ilmiah Sekolah Dasar, 2018)
This study aims to determine the significant differences in the mastery of science knowledge competence group of students who are taught by the model problem based learning of audio visual media with groups of students who are taught through conventional learning in fourth grade students of SD Dewi Sartika Denpasar Clinic School Year 2016/2017. This research type is quasi experiment research with nonequivalent control group design. The population of this study is all students of grade IV SD Dewi Sartika Denpasar Elementary School, amounting to 374 students. Samples were taken by random sampling technique. The sample in this research is the fourth grader of SDN 3 Kesiman amounting to 40 students as the group which is taught by the model problem based learning assisted by Audio Visual media and the fourth grade students of SDN 17 Kesiman is 40 students as control group with conventional learning. The data were collected using a test method in the form of a standard multiple-choice objective test with four answers. The data obtained were analyzed using t-test analysis. The result of data analysis is obtained tvalue = 6,573> ttable = 2,000 for 5% significance and dk = 78. Based on testing criteria, H0 is rejected and Ha accepted. Based on the results of this study can be concluded that there is the influence of problem based learning modeled audio visual media on the mastery of science knowledge competence of fourth grade students SD Gugus Dewi Sartika Denpasar Academic Year 2016/2017